Analisis Karakteristik dan Rencang Bangun Sistem Ekonomi Islam - Aulia Wulandari; Jihan Laila Barokah; Rosita Rosita; Yulischa Putri Utami; M. Yusuf Bahtiar (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The development of modern economic systems shows that conventional approaches are often criticized for focusing too much on rational and mathematical aspects, while giving less attention to ethical and moral values in economic activities. This condition has encouraged the emergence of alternative systems that combine material and spiritual elements, one of which is the Islamic economic system.This study aims to analyze the characteristics and structure of the Islamic economic system as a framework based on Sharia principles. The research uses a qualitative approach with a literature review method by examining various relevant sources. The data are analyzed descriptively to better understand the basic concepts and structure of the Islamic economic system.The results show that Islamic economics has key characteristics such as a strong connection to divine values, a balance between individual and social interests, and an emphasis on justice and social responsibility in economic activities. Therefore, Islamic economics not only regulates economic practices but also incorporates moral and ethical values to achieve overall social well-being.This study is expected to contribute to the development of Islamic economic studies and can be used as a reference for building a more fair and sustainable economic system.